2019
DOI: 10.1016/j.triboint.2019.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between wall slip and cavitation: A complementary variable approach

Abstract: In this work a stable and reliable numerical model based on complementary variables is developed to study lubricated contacts characterised by slip at one or both surfaces and in the presence of cavitation. This model can be used to predict surface behaviour when cavitation induced by e.g. the presence of surface texture, slip, or a combination of the two is encountered, with varying surface parameters. For this purpose, two different algorithms are coupled to predict the formation of cavitation, through a mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Their main finding was that the enhanced tribological performance of journal bearing could be achieved with well-designed slip/texture surface. In recent lubrication, using numerical model based on complementary variables, Biancofiore et al [21] reported that a very large increase in the pressure profile and significant decrease in friction coefficient are registered by introducing slippage.…”
Section: Introductionmentioning
confidence: 99%
“…Their main finding was that the enhanced tribological performance of journal bearing could be achieved with well-designed slip/texture surface. In recent lubrication, using numerical model based on complementary variables, Biancofiore et al [21] reported that a very large increase in the pressure profile and significant decrease in friction coefficient are registered by introducing slippage.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the effect of boundary slip and surface texturing was also studied, for example [8,16,19,20,[43][44][45][46][47][48], but ignoring the cavitation effect and mostly using a non-massconservation cavitation equation. In the present work, it will be shown that cavitation has a strong influence on performance and unrealistic conclusions may be drawn if the cavitation is ignored.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allowed sub atmospheric and even negative pressures, no matter how low they were [47]. In 1914, Gumbel [48] was the first to account for the film 'rupture'. According to his theory, for a steadily loaded bearing operating at constant angular velocity, the rupture originates in the immediate vicinity of the film's minimum clearance at a predetermined pressure pcav and remains constant at that value for the entire divergent region (Fig.…”
Section: Half Sommerfeld (Gumbel) Cavitation Modelmentioning
confidence: 99%
“…The more elusive problem in dealing with film rupture has been respecting the mass continuity within the confines of the Reynolds equation. Gumbel's condition [48] and the half Sommerfeld condition did not respect the continuity of mass; they just accounted for the fact that when and where the film ruptured, pressures became sub ambient (negative) and consequently automatically set to pcav in the final iteration (SS/ Gumbel) and every step in the full-film zone in the cavitated area iteration (HS). Today, the mass conservation cavitation has been used to analyse cavitation events.…”
Section: Mass Conserving Cavitation Modelmentioning
confidence: 99%
See 1 more Smart Citation